ASSESSMENT OF PATIENT SATISFACTION WITH MENTAL HEALTH SERVICES IN A TERTIARY CARE SETTING - Gani, Naveed; Saeed, Khalid; Minhas, Fareed Aslam; Anjuman, Nigar; Waleed, Maria; Fatima, Ghulam (Journal of Ayub Medical College Abbottabad, 2011)
Background: Patients’ opinion regarding services has acquired great importance. Patient satisfaction is playing an increasingly important role in quality of care reforms and health-care delivery. The study aimed to measure patient satisfaction in a tertiary care hospital in order to know the patients’ perspectives and expectations of the services and make appropriate improvements accordingly. Methods: This was a crosssectional study conducted at the Out-patient and Inpatient Departments of the Institute of Psychiatry, Benazir Bhutto Hospital, Rawalpindi, for a period of 8 months from October 2008 till June 2009. Sample size was 246 patients; which included 123 participants from Out-patient and In-patient departments each. Patients aged 18 and above, of both genders, who gave informed written consent, were consecutively recruited for the study. Learning disabled patients, frankly psychotic and those with severe cognitive impairment and severe co-morbid physical illnesses were excluded. Performa was filled in by the participants for their demographic details. The Client Satisfaction Questionnaire-8 was then orally administered in the native language (Urdu/Punjabi) to assess the degree of patient satisfaction. Results: Among the participants, 72% were mostly satisfied, 18.7% mildly satisfied and 9.3% dissatisfied with the psychiatric care. Age was significantly associated with satisfaction however no such associations could be found for gender and economic status. Conclusion: Majority of the patients were satisfied with the psychiatric services. The younger people were more satisfied. Gender and economic status had no influence on patient satisfaction. Keywords: Patient satisfaction, Quality of Health Care, Patient compliance, Mental Health Services